2021
DOI: 10.12792/jmti.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Foreign Language Anxiety and Willingness to Communicate Among Japanese EFL Learners

Abstract: She has years of experience in teaching English at high school, vocational school and university. She is currently a researcher at Hokkaido University. Her research interests include language anxiety, willingness to communicate (WTC), individual factors, and EFL teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Based on the research results, the higher level of anxiety in an Arabic language classroom, the more reluctant the learners will be to communicate in the class, and if their anxiety decreases, the more they are willing to communicate. The current study's findings are in accordance with the previous studies (Fujii, 2021;Rastegar & Karami, 2015;Tabataba'ian & Birjandi, 2012). Similarly, Baran-Lucarz (2014), who emphasised pronunciation anxiety, discovered that the more anxious the participants were about their pronunciation, the less eagerly they participated in speaking activities in the foreign language classroom.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the research results, the higher level of anxiety in an Arabic language classroom, the more reluctant the learners will be to communicate in the class, and if their anxiety decreases, the more they are willing to communicate. The current study's findings are in accordance with the previous studies (Fujii, 2021;Rastegar & Karami, 2015;Tabataba'ian & Birjandi, 2012). Similarly, Baran-Lucarz (2014), who emphasised pronunciation anxiety, discovered that the more anxious the participants were about their pronunciation, the less eagerly they participated in speaking activities in the foreign language classroom.…”
Section: Discussionsupporting
confidence: 93%
“…They argued that less anxious learners are inclined to have higher levels of intention to communicate. Fujii (2021) looked into the correlations between foreign language anxiety and willingness to communicate, the differences in willingness to communicate between high-anxious and low-anxious learners, and learners’ intention to communicate effectively in educational contexts. His study found a significant, negative relationship between foreign language anxiety and willingness to communicate, and the differences between high-anxious and low-anxious learners in terms of willingness to communicate were significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, in accordance with the findings of a slew of studies, foreign language anxiety is indeed a massive concern and commonly an adverse consequence that may hamper a person's foreign language (FL) acquisition (Alqurashi & Althubaiti, 2021;Cui, 2020;Alaleh, 2018;Dewaele & MacIntyre, 2016). Foreign language anxiety (FLA) is thought to be crucial and compelling in predicting foreign language achievement of EFL learners, principally in speaking skill and communication competence in institutional and highly qualified academic contexts Fujii, 2021;Effiong, 2015). By comparison, Kiae et al (2021) postulated that English-language anxiety corresponds to a form of social anxiety largely dependent on interpersonal interactions.…”
Section: Background and Problem Statementmentioning
confidence: 81%